PERBEDAAN PENYESUAIAN DIRI SANTRI DI PONDOK PESANTREN TRADISIONAL DAN MODERN - Hidayat, Dyah Aji Jaya (TALENTA, 2012)
Living in borading school disciplin and strict activity schedules, demanding that students should be able to adapt to survive in the environment. In while, the student are also required to be independent living separately from parents Dhofier (1985) divided into two types of boarding schools: traditional (salafi) and modern (khalafi). The differences in the two lies in how to teach, the pattern relations between student and teachers, as well as learning level.The aimed of this study was to determine whether there are difference in adjustments to the traditional boarding school students and modern. Subjects in this study are a members of boarding school students amount 96 persons. Purposive Random Sampling was used to measuring a scale of adjustment and then analyzed by ANAVA 2 ways. The data analysis showed that F score between A said 42,082 (p = 0,000 or p < 0,01). Mean that there is a significantly differences in adjustments to the traditional boarding school students shows better adjustment than the modern ones. It showed from the adjustments average level for traditional boarding school students (A1) = 138,413 and the modern ones average level (A2) = 116,860. The empirical mean for adjustments variabel is 127,188 and hypothetical mean is 115. It is also showed that both traditional or modern ways are in medium adjusments level.